Managing Religious Diversity in Nigerian Secondary Schools: Implications for Educational Policy, Interfaith Dialogue, and Social Cohesion - Kamaldeen Ibraheem Nageri (International Journal of Social Science and Religion (IJSSR), 2026)
Religious diversity is a defining characteristic of Nigeria’s social structure and has significant implications for the education system. Schools often serve as primary spaces where students from different religious backgrounds interact, making the management of religious diversity critical for promoting tolerance and social harmony. This study examines how Nigerian schools manage religious diversity and the implications for educational policy and social cohesion. Using a qualitative research design, data were collected through semi-structured interviews with teachers, school administrators, and education policy stakeholders, complemented by document analysis of national education policies and curriculum frameworks. The findings indicate that inclusive curricula, interfaith dialogue initiatives, and teacher training in religious ethics contribute significantly to fostering tolerance and peaceful coexistence among students. However, challenges such as community resistance, inadequate policy enforcement, and limited professional training continue to hinder effective management of religious diversity in schools. The study highlights the importance of strengthening policy frameworks, improving teacher preparedness, and integrating pluralistic perspectives into educational curricula. Ultimately, effective management of religious diversity within schools can enhance social cohesion, promote national integration, and contribute to long-term socio-economic development in Nigeria.